Affectedness, Subjection and Climate Change. A critical account of Nancy Fraser’s All-Subjected Principle - Ibañéz, Franklin (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
Globalization benefits especially few powerful agents, such as transnational corporations, to the detriment of others, such as the global poor. To remedy this situation, Nancy Fraser prefers the all subjected principle, which states that all those who are subject to a given governance structure have moral standing as subjects of justice in relation to it. This article argues that Fraser’s proposal is inadequate, because it departs from a misguided diagnostic: assuming the existence and proper functioning of transnational governance structures that control the main processes of globalization. The hypothesis is confirmed by analyzing the implementation of governance structures to rule climate change.
Keywords: globalization; global justice; climate change; Nancy Fraser